Pembelajaran PAI Berbasis Media Digital Untuk Mengembangkan Kemampuan Berpikir Kritis Peserta Didik di Abad 21 - Nurul Azizah; Krisna Wijaya; Nida Rafiqa Izzati (At Turots: Jurnal Pendidikan Islam, 2024)
Today, Islamic religious education faces great challenges with the presence of the technological era that exists in the midst of humans. Among the problems that occur today is that Islamic religious learning in elementary schools has not been maximized in an effort to improve the critical thinking skills of its students. This study seeks to explain various media innovations that can be used in religious learning to improve the critical thinking skills of students in elementary schools. This critical thinking ability is very important and so important in today's era of digital development. This study was reviewed using systematic literature review techniques. The data analysis technique used in this study is content analysis. The results of this study found that various forms of digital media that can be used and utilized in PAI learning in the digital era to improve the ability of critical thinking skills are visual, auditory, web, video, VisIDi-MIPAI, social media, skype, zoom, google, web based learning, digital comics, augment reality, canva, e-books, internet, and digital learning platforms on the internet.